A RESEARCH SURVEY ON SCHEDULING TECHNIQUES IN LTE-BASED NETWORK AND ITS STATE OF ART - K, Srinivasa R; A.R2, Hemantha Kumar (APTIKOM Publisher, 2018)
The growing interest over the mobile based communication has attracted the Long-Term Evolution (LTE)technique which facilitates higher data transmission rates to its dynamic users. The LTE-based network involves withscheduling which governs the better communication at different traffic (large, small, medium) condition. The LTEcaters up network demands and encounters some potential and unreported problems in presence of large traffic withuncertainty of its associated load. Thus, scheduling becomes most essential is must. This manuscript reviews the recentexisting researches with their contribution along with significances and limitations. The paper also contributes inidentify the state of art in research issues to identify the research gap towards scheduling techniques in LTE